Challenges Faced by Participants in the In-service Teacher Certification Programme - Ni Putu Meita Subudiasih; Putu Suarcaya; Ni Putu Era Marsakawati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
In order to better equip teachers for the profession, this research looks at the difficulties encountered by those who take part in Indonesia's Teacher Professional Education Program (PPG). The purpose of this research is to learn about the difficulties encountered by PPG members and the strategies they used to overcome them. A qualitative technique is utilized in this study's methodology. Ten teachers who had finished the PPG program at Ganesha University of Education in 2020 were involved in this research. In this study, internet interviews served as the data collection tool. There were five steps to the data processing process in this study: reading, transcribing, highlighting, keywords, and categorization. Problems with technology adoption and insufficient technical knowledge were identified as difficulties experienced by PPG members in this survey. not having a complete grasp of software expertise, being confused when selecting assessment tools, and having trouble creating lesson plans. Participants work on their problem-solving skills by studying on their own or using the YouTube app. The study's findings suggest that participants might utilize their experiences with the obstacles they faced to better prepare for the future of technology in online education.